A sonication-assisted method for the production of true-to-life nanoplastics from polymeric materials - Carlos Adelantado; Jasper Charlier; Nancy Dewit; Jan Jordens; Stefan Voorspoels; Kristof Tirez; Milica Velimirovic (Nano Express, 2025)
Worldwide plastic production has surpassed four hundred megatons over the last two years, this trend steadily rising and making plastic become one of the more serious environmental pollutants. While a wide knowledge is already existing about macroplastics, a recent and complex problem to tackle is degradation of these materials to micro- and nanoplastics. It has been demonstrated that organisms react in a different way to naturally degraded nanoplastics (NPs) when compared with NPs produced in the laboratory, the artificially created ones being more widely reported in research studies. As a consequence, new approaches need to be orientated towards NP release mimicking particles produced in the environment. The objective of this study is to develop and optimize a sonication-assisted method for degrading macroplastics and generating NPs from different real-life polymeric sources. Specimens of use were tire treads, polyethylene terephthalate (PET) bottles, high-density polystyrene (HDPS) and low-density polyethylene (LDPE). Special attention was paid to lessening the workload in the laboratory and minimising both contamination and thermal degradation. Every plastic-based item was cryogenically milled, and small amounts of the resulting powder were suspended in water and subjected to ultrasound treatment in a bath with an applied ultrasonic energy density of 7.0 kJ ml ^−1 (equivalent to 64 h of sonication at 160 W). Particle sizing was primarily performed with dynamic light scattering. Whereas LDPE showed a little sign of nanoparticle production, possibly due to energy input, PET and tyres released quantifiable amounts of nanoparticles after receiving 5.2 kJ ml ^−1 (equivalent to 48 h of sonication at 160 W) of ultrasonic energy density. Hydrodynamic diameters varied from 150 up to 300 nm for these two polymers. It was hypothesised that additives may prevent degradation to a certain extent, thus highlighting the necessity for increasing the total applied ultrasonic energy to promote plastic degradation.